2020
DOI: 10.3390/plants9030363
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Response Mechanism of Soil Salinity-Induced Cross-Tolerance to Subsequent Drought Stress in Tomato Plants

Abstract: Soil salinization and water shortage cause ion imbalance and hyperosmoticity in plant cells, adversely impairing photosynthesis efficiency. How soil salinity-induced photosynthetic acclimation influences the cross-tolerance to drought conditions represents a promising research topic. This study was to reveal the photosynthetic mechanism of soil salinity-induced resistance to the subsequent drought stress in tomato leaves through comprehensive photosynthesis-related spectroscopy analysis. We conducted soil sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…In general, plants irrigated with highsalinity water tend to exhibit morphological, physiological, biochemical and molecular alterations to survive in stressful environments, through mechanisms of accumulation of osmoprotectants, water use efficiency, enhanced photosynthesis, detoxification of reactive oxygen species (ROS) and phytohormone induction (Evelin, Devi, Gupta, & Kapoor, 2019;Dias et al, 2018a;Fricke, 2020). Nevertheless, these adaptive strategies are inefficient to cope with the osmotic and ionic effects, which induce a reduction in chloroplast pigments and in the photosynthesis, growth and production of crops (Yang et al, 2020). Oliveira et al (2018) found that irrigation with 4.5 dS m-1 saline water reduces growth and production in bell pepper.…”
Section: Introductionmentioning
confidence: 99%
“…In general, plants irrigated with highsalinity water tend to exhibit morphological, physiological, biochemical and molecular alterations to survive in stressful environments, through mechanisms of accumulation of osmoprotectants, water use efficiency, enhanced photosynthesis, detoxification of reactive oxygen species (ROS) and phytohormone induction (Evelin, Devi, Gupta, & Kapoor, 2019;Dias et al, 2018a;Fricke, 2020). Nevertheless, these adaptive strategies are inefficient to cope with the osmotic and ionic effects, which induce a reduction in chloroplast pigments and in the photosynthesis, growth and production of crops (Yang et al, 2020). Oliveira et al (2018) found that irrigation with 4.5 dS m-1 saline water reduces growth and production in bell pepper.…”
Section: Introductionmentioning
confidence: 99%
“…Salt stress induces various biochemical and physiological responses in plants and affects most of plant metabolic processes [ 1 , 4 ]. Alterations in the integrity of cell membranes [ 5 ], as well as inhibition of different enzymatic activities and photosynthesis [ 6 , 7 , 8 ], are among the main processes affected. In addition, plants exposed to saline soils trigger generation of reactive oxygen species (ROS), which in turn have a negative oxidative stress effect on cellular structures and metabolism [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with other studies on the effects of saline stress and water deficit on photosynthesis (Chen et al, 2016 , 2017 ; Yi et al, 2018 ; Tsai et. al., 2019 ; Grieco et al, 2020 ; Yang et al, 2020 ; see also review by Acosta-Motos et al, 2017 ). Interestingly, in the snrk2.10 lines, the changes appeared earlier than in wt plants indicating that the excitonic pressure-inducing mechanisms dissipating excess of absorbed light energy was higher in those lines.…”
Section: Discussionmentioning
confidence: 99%